A Content Analysis of the TikTok Account @amiirahanugrah: The Representation of Halal Food at 7-Eleven Stores in Thailand - Mochammad Abdul Machfud; Asidigisianti Surya Patria; Abdul Hafidz; Nova Kristiana; Arieviana Ayu Laksmi; Yunia Dwie Nurcahyanie; David Nugroho (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The rise of TikTok is particularly relevant in the food industry, where engaging visual content communicates product appeal. This study analyzes how halal food is represented in the TikTok account @amiirahanugrah, specifically regarding 7-Eleven Thailand products. The purpose is to identify the main themes and strategies used in presenting halal food. Using qualitative content analysis on three selected videos, the study reveals that the creator effectively acts as a "micro-halal ambassador" by integrating Islamic values into lifestyle content. The main findings indicate that halal perception is co-constructed through three key strategies: (1) the use of verbal religious expressions (e.g., Bismillah, Alhamdulillah) in non-ritual contexts; (2) visual transparency by displaying halal logos and ingredients; and (3) the demonstration of Islamic etiquette (adab) such as handwashing. Furthermore, audience analysis shows a mechanism of "social halal validation," where followers rely on trust in the creator's consistent persona and emotional tone rather than demanding formal verification, thereby effectively promoting cross-cultural halal tourism.